Exploring the relationship between social support and self-esteem for adolescent cancer survivors - Katie Walker; Christine Lippard (Cancer Survivorship Research & Care)
Despite the growing attention to psychosocial survivorship outcomes for adolescent cancer survivors (ACS), little is known about how different sources of support – particularly peer versus parent support – are uniquely related to ACS specific aspects of self-esteem. This gap is critical to address, as self-esteem is a core developmental task of adolescence, and may be differentially affected both by cancer experience and social context. In this study, data was collected from 77 ACS (ages 11-19) who completed perceived social support and self-esteem measures at an oncology camp. Results revealed that ACS who reported higher perceived social support reported higher self-esteem. Both peer and parent support were significantly related to all three self-esteem domains: performance, appearance, and social. Contrary to prior research suggesting parental support is more infuential, our findings suggest that peer and parent support are equally important across all self-esteem domains. Overall, these findings highlight the importance of integrating peer-based support interventions in patient care to enhance the psychosocial well-being of adolescent cancer survivors.